Development Of A Spatial Web-Based Graphical User Interface With Gis For Real Estate Users - Al-Hader, Mahmoud Fawzi (2007)
Geographic information is a valuable source for applications and analysis, where location of objects and events, can enhance the decision making activities. Recently, the interoperability of geospatial data has been an ongoing research activity and goal of the geospatial information user community for decades. Focusing on data integration scenarios, the recent popularity and adoption of the internet and web services, has provided a new means of interoperability for geospatial information, differing from previous approaches to information exchange. Currently the interoperability approaches of geospatial information with real estate data are inadequate. This thesis argues that utilizing the interoperability real estate data, with geospatial data using web services, is the best method to achieve efficient data exchange than traditional approaches. The thesis demonstrates this by developing a spatial web service to facilitate transferring data, from real estate users, to Geographic Information System (GIS) data layers. The thesis also discusses how web services affect data preparation and data updating. Various scenarios of geocoding and transferring real estate data into geospatial data will be discussed. A web interface implementation is presented, to illustrate the validity of the interoperable spatial web service approach, with real estate for which this thesis argues. The interface has two ways communication. On one hand users will be able to use the spatial web service to integrate the property data, with GIS service provider. On the other hand, user will be able to receive a map report for the geocoded property.